Longitudinal growth of children born with gastroschisis or omphalocele - Tauriainen Asta; Harju Samuli; Raitio Arimatias; Hyvärinen Anna; Tauriainen Tuomas; Helenius Ilkka; Vanamo Kari; Saari Antti; Sankilampi Ulla (Germany, 2025)
Normal childhood growth is an indicator of good health, but data addressing the growth of children born with abdominal wall defects (AWDs) are limited. The detailed growth phenotypes of children born with gastroschisis or omphalocele are described and compared to peers without AWDs from birth to adolescence. Data from 183 gastroschisis and 144 omphalocele patients born between 1993 and 2017 were gathered from Finnish nationwide registers and electronic health records. Weight (n = 3033), length/height (n = 2034), weight-for-length (0-24 months, n = 909), and body mass index measures (2-15 years, n = 423) were converted into sex- and age-specific Z-scores. Linear mixed models were used for comparisons. Intrauterine growth failure was common in infants with gastroschisis. Birth weight Z-scores in girls and boys were - 1.2 (0.2) and - 1.3 (0.2) and length Z-scores - 0.7 (0.2) and - 1.0 (0.2), respectively (p < 0.001 for all comparisons to infants without AWDs). During early infancy, growth failure increased in infants with gastroschisis, and thereafter, catch-up growth was prominent and faster in girls than in boys. Gastroschisis children gained weight and reached their peers' weights permanently at 5 to 10 years. By 15 years or older, 30% of gastroschisis patients were overweight. Infants with omphalocele were born with a normal birth size but grew shorter and weighing less than the reference population until the teen-age years.
Conclusion: Children with gastroschisis and omphalocele have distinct growth patterns from fetal life onwards. These growth trajectories may also provide some opportunities to modulate adult health.
What is known: • Intrauterine and postnatal growth failure can be seen frequently in gastroschisis and they often show significant catch-up growth later in infancy. It is assumed that part of the children with gastroschisis will become overweight during later childhood.
What is new: • The longitudinal growth of girls and boys with gastroschisis or omphalocele is described separately until the teenage years. The risk of gaining excessive weight in puberty was confirmed in girls with gastroschisis.